Inherited prothrombotic states and ischaemic stroke in childhood. Issue 4 (1st October 1998) - Ganesan, V; McShane, M A; Liesner, R; Cookson, J; Hann, I; Kirkham, F J
Abstract : OBJECTIVE: To investigate the prevalence of currently recognised inherited prothrombotic states in a population of children with arterial stroke. METHODS: Children with arterial stroke presenting to a tertiary level paediatric neurology centre between 1990 and 1996 were investigated for inherited prothrombotic states. RESULTS: Sixty seven children with arterial stroke were investigated. Abnormalities were initially identified in 16 patients; however, only eight children (12%) had an inherited prothrombotic state. This was type 1 protein S deficiency in one patient, the factor V Leiden mutation in six, and activated protein C resistance (without the factor V Leiden mutation) in one. The prevalence of the factor V Leiden mutation was not significantly higher in children with arterial stroke (12%) than in a control population of children without thrombosis attending the same institution (5.2%; Fisher's exact test, p=0.19; difference in prevalence between patients and controls (95% confidence interval)=6.8% (−2.78% to 16.8%)). CONCLUSIONS: Currently recognised inherited prothrombotic tendencies were rarely associated with stroke in this group of children, although larger numbers of patients would be needed to confirm this. Age appropriate normal values should be used when interpreting the results of a prothrombotic screen. Prothrombotic abnormalities seen acutely are as often transient as inherited. Longitudinal assessment and family studies are required before low concentrations of an anticoagulant protein found acutely can be attributed to an inherited abnormality.